Probable case of spotted fever group rickettsial infection in a new suspected endemic area, Colombia (2023)
Spoted fever group (SFG) rickettsioses are actually considered as emerging and re-emerging zoonotic diseases, caused by pathogenic bacteria of the spotted fever group rickettsiae (SFGR). Recently.